A New Filtered Alcoholic Beverage: Residues Evidence From the Qingtai Site (ca. 5,500–4,750 cal. BP) in Henan Province, Central China - Liao, Jingwen; Yang, Yuzhang; Gu, Wanfa; Yao, Ling; Wei, Qingli; Luo, Wuhong; Gong, Yingxue; Ding, Lanpo; Gu, Chunguang; Zhang, Juzhong (Frontiers in Earth Science, 2022)
Recent studies have provided evidence of alcohol production and consumption in 16 sites in northern China during the Neolithic period, focusing on the Yangshao Culture (ca. 7000-5000 cal. BP). Yet, the comparison of similarities and differences in brewing technology and drinking patterns within the Yangshao Culture still needs more supporting information from case studies in different regions. In this paper, 17 pottery samples excavated from the Yangshao Culture site of Qingtai (ca. 5500-4750 cal. BP) in the central part of Henan Province were analyzed for microfossils (starch grains, phytoliths, fungi) and organic acids, on the basis of the theoretical model constructed from our simulation experiments. The results revealed a mixed filtered alcoholic beverage, likely to be fermented by fruit and/or honey. The ingredients were mainly foxtail millet, rice, Job’s tears, Triticeae, snake gourd roots, lotus roots, legumes, nuts, fruits, and/or honey. What’s more, we found that the jiandiping amphora from Qingtai was not likely used for brewing or drinking. In terms of prehistoric drinking habits, in the large-scale settlement of the late Yangshao Culture in China, it is possible that people drank filtered alcohol alone or that a few people drank filtered alcohol poured from the painted bottle, indicating a switch from communal drinking to individual drinking. This study sheds light on the similarities and differences in brewing techniques, fermentation ingredients, and drinking patterns among different regions of the late Neolithic Yangshao Culture, and deepens our understanding of alcoholic beverages in the early Chinese civilized societies.